Improvement in the effective cataract surgical coverage in Malaysia: evidence of impact from a mobile cataract outreach program - Mohamad Aziz Salowi; Nyi Nyi Naing; Norasyikin Mustafa; Wan Radziah Wan Nawang; Siti Nurhuda Sharudin; Mohd Aziz Husni (BMC Public Health)
Abstract Background Effective Cataract Surgical Coverage (eCSC) is one of the Universal Health Coverage (UHC) indicators recommended by the World Health Organization (WHO). It is calculated from a population survey and measures access and quality of eye care services in the community. We conducted simultaneous population-based eye surveys in two regions in Malaysia in 2023 to estimate eCSC and compare the results with the survey in 2014 following the implementation of a mobile cataract program. Methods The surveys were simultaneously done in Eastern and Sarawak administrative regions using the Rapid Assessment of Avoidable Blindness (RAAB) technique. It involved a multistage cluster sampling method, each cluster comprising 50 residents aged 50 years and older. Presenting visual acuity (PVA) was checked, and subjects with cataracts were identified. The corrected VA (Pinhole) of those who had undergone cataract surgery was measured. eCSC was calculated at all levels of cataract surgical thresholds according to the protocol. The findings were compared with the previous survey. Results A total of 10,184 subjects were enumerated, with 9,709 examined and 475 non-respondents. Females had a significantly lower Cataract Surgical Coverage (CSC) than males for cataract surgical threshold of < 3/60 for both regions in National Eye Survey (NES) II in 2014, [Eastern female 82.0%, 95% Confidence Interval (CI) (72.5, 91.5) vs. male 97.8%, 95% CI (92.8, 100.0), Sarawak female 76.9%, 95% CI (66.4, 87.3) vs. male 96.4%, 95% CI (91.6, 100.0)]. However, there was no significant gender difference in eCSC. Comparing NES II (2014) and NES III (2023) at various levels of cataract surgical threshold, eCSC improved within the range of 13.8-19.2% and 18.6-23.8% for Eastern and Sarawak, respectively. Conclusion The improvement in eCSC could likely be attributed to both quality outcome enhancement and increased coverage, possibly due to the impact of the mobile cataract services in both regions. However, a coordinated approach is necessary to further strengthen and expand the coverage of the program to enable the country to achieve the 30% increase in eCSC as targeted by WHO.